Out-migration prospects, changing values and young people's increasing disinterestedness in cocoa farming in Southwest Nigeria (2016)
The paper engages the contradiction wherein in the face of unemployment in its several strands young people in cocoa farming communities in Southwest Nigeria exhibit strong aversion for farming activities. Anchored on Rational Choice Theory and Ethno-methodology the study adopted the qualitative data collection techniques including In-depth Interviews, Key Informant Interviews and Focus Group Discussions. Findings show that prospects for out-migration to urban centres to undertake other livelihood activities, perceived capital and labour intensity, low prestige and derogation ascribed to cocoa farming were identified as major reasons for dwindling interest of young people in cocoa farming. It is strongly recommended that government should reposition agriculture generally and cocoa farming in particular by creating a genuine enabling environment to reawaken the interest of young people to cocoa business.